LPG Batch Oven with PID control for the automation of the electrostatic paint curing process. - Palomares Orihuela, Ricardo John (2024)
This article presents the improvement of the surface coating process with electrostatic painting by manufacturing an LPG batch-type curing oven with a working volume of 20 m³. The structure was manufactured with 3/16” x 2” structural angles, sandwich panels made of 0.6 mm and 1.0 mm galvanized steel sheets and with a 2” thick wool interior as insulation. 6 LPG catalytic infrared burners were used with a total power of 65.4 kW/h, with which the temperature of 180 °C was reached in 20 minutes with maximum load. A graphical interface was designed with a touch screen. A Raspberry Pi 3B+ was used to run the control and monitoring software developed in Python. Industrial PID temperature controllers and three-wire PT-100 sensors were used. Mathematical modeling of the oven was carried out to obtain the transfer function and tuning constants of the PID controller. Nine tests were carried out to ensure proper operation of the oven. Sample sheets with thicknesses from 90 µm to 106 µm were painted and cured, which guarantees the durability of the applied paint. Finally, adhesion, scratching, bending and sanding tests were carried out, obtaining optimal results in each one.